Concurrent onset of acute lupus myocarditis, pulmonary arterial hypertension and digital gangrene in a lupus patient: a possible role of vasculitis to the rare disorders. (2nd January 2020) - Ando, Takayasu; Yamasaki, Yoshioki; Takakuwa, Yukiko; Iida, Harunobu; Asari, Yusa; Suzuki, Kanako; Uchida, Marina; Kotoku, Nozomi; Tanabe, Yasuhiro; Chosokabe, Motohiro; Takahashi, Masahide; Suzuki, Kengo; et al.
Abstract: Acute lupus myocarditis and pulmonary arterial hypertension (PAH) are rare complications associated with systemic lupus erythematosus (SLE). No previous reports have shown the coexistence of these disorders. Here we present a 41-year-old patient with SLE who concurrently developed severe acute lupus myocarditis and PAH with digital gangrene as an initial manifestation. Acute lupus myocarditis and PAH were successfully treated with prednisolone and intravenous cyclophosphamide pulse therapy (600–700 mg × 6) along with anticoagulant therapy. Catheter-directed thrombolysis was required for digital gangrene caused by vasculitis. Concurrent development of these rare disorders may represent a common mechanism such vasculitis as an underlining cause of SLE.